An analysis on how can AI empower the senior population in their access to banking services - Alfaro Peral, Yolanda (2022)
This article addresses the banking interaction needs of the senior population, devoting special attention to the unique needs of this age demographic delineated by the natural cognitive decline caused by ageing. Despite being a compelling business audience, the financial sector, and particularly banking institutions, have significantly underestimated the importance of designing a customer experience that is better adapted to the needs of senior users. A compelling yet achievable solution to this problem is the adoption of AI-based technologies, such as dynamic user interfaces, biometric authentication methods, automatic recommendations, and experience-based APIs. The curated adoption of these tools will enable banks to better serve this increasingly growing population by creating seamless and respectful experiences for their senior customers and, above all, will provide them greater autonomy.